2015
DOI: 10.1063/1.4914973
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging without field cycling at less than earth's magnetic field

Abstract: A strong pre-polarization field, usually tenths of a milli-tesla in magnitude, is used to increase the signal-to-noise ratio in ordinary superconducting quantum interference device-based nuclear magnetic resonance/magnetic resonance imaging experiments. Here, we introduce an experimental approach using two techniques to remove the need for the pre-polarization field. A dynamic nuclear polarization (DNP) technique enables us to measure an enhanced resonance signal. In combination with a p=2 pulse to avoid the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…However, we demonstrated that circularly polarised RF results in a substantially higher enhancement factor of over 150,000 at 1.2 µT and can be implemented with a birdcage coil. The magnetic field applied for O-DNP was only 1.2 µT (B p ), which is approximately 30 times lower than 34.5 µT in our previous work [29]. However, the quality of the image ( Fig.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…However, we demonstrated that circularly polarised RF results in a substantially higher enhancement factor of over 150,000 at 1.2 µT and can be implemented with a birdcage coil. The magnetic field applied for O-DNP was only 1.2 µT (B p ), which is approximately 30 times lower than 34.5 µT in our previous work [29]. However, the quality of the image ( Fig.…”
Section: Resultsmentioning
confidence: 63%
“…The total acquisition time constituted to 77 min. The phantom in the present work is the same as in our previous study [29] and was filled with a 2 mM TEM-POL (4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl) solution which seemed to achieve the optimal result in the microtesla field range [30,31]. It has the dimensions of 54 mm * 43.5 mm * 40 mm, featuring a letter K in the middle as well as rectangles and circles with varying sizes (top 10 mm, middle 5 mm, bottom 3 mm) on the left and right sides, respectively.…”
Section: Overhauser-enhanced Mrimentioning
confidence: 99%
“…In addition, to obtain a good MR image in SQUID-based microtesla MRI, a pre-polarization field ( B p ) is required before the MR signal from the sample is detected. Therefore, some attempts 17,22,23 were made to obtain a strong B p , including optimizing the B p coils and cooling these coils to reduce noise. Increasing B p using a coil also yielded critical effects: the generation of eddy currents on the walls of a magnetically shielded room (MSR) 24,25 and flux trapping in a pickup coil 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The hyperpolarization technique can solve this pre-polarization problem to enable the polarization of materials with an extremely high order of magnitude. There have been several recent reports 18,22,2730 on this strategy. The most well-known way of achieved hyperpolarization, DNP, which is used to transfer polarization from electrons to nuclei, was harnessed to obtain a high-contrast microtesla MR image 18,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation